2011
DOI: 10.3166/ejece.15.461-485
|View full text |Cite
|
Sign up to set email alerts
|

Progress in ultrasonic tendon duct imaging

Abstract: Ultrasonic imaging of tendon ducts enables the precise localisation of grouting faults in many cases. Additionally to well known criteria for detecting grouting faults in tendon ducts new possibilities were developed recently: Phase value evaluation for qualitative distinction between steel and air reflection and analysing backscatter from the area of bottom side of tendon ducts.The application of linear array technique enables much faster data acquisition and data analyses. Examples and comparison with automa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…The presence of vertical cracks leads to a reduced modulus of elasticity of concrete, which can be captured using the ultrasonic surface wave method [67]. Delamination can be detected using impact echo [68,69], pulse echo [70]; and infrared thermography tests [71,72]. Table 3 The use of simple NDE tools such as chain drag and hammer sounding is the predominant practice of condition assessment of concrete bridge decks.…”
Section: Nde Techniques For Concrete Bridge Decksmentioning
confidence: 99%
“…The presence of vertical cracks leads to a reduced modulus of elasticity of concrete, which can be captured using the ultrasonic surface wave method [67]. Delamination can be detected using impact echo [68,69], pulse echo [70]; and infrared thermography tests [71,72]. Table 3 The use of simple NDE tools such as chain drag and hammer sounding is the predominant practice of condition assessment of concrete bridge decks.…”
Section: Nde Techniques For Concrete Bridge Decksmentioning
confidence: 99%
“…In order to overcome this problem, special transducers and imaging methods based on array techniques and synthetic aperture are applied. They have originally been developed for ultrasonic 13testing of concrete elements (and are continuously improved) in research and development activities [17,18,19,5]. Some applications for timber are described in section 2.4.2.…”
Section: Reflection Of Ultrasonic Wave Pulsesmentioning
confidence: 99%
“…Successful imaging of defects, using SAFT in materials like composites and concrete through numerical simulation and experimental investigation has been reported in [11][12][13][14]. Recent developments in the field of synthetic aperture imaging of concrete involve the application of 2D arrays [15][16][17][18] which employ shear waves for interrogation of the medium. Condition monitoring of tendon ducts using shear wave transducer arrays has been reported in [16,17], wherein the SAFT generated C-scan images of the scattered field are used to identify the embedded artificial defects as steel plate or air-voids.…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in the field of synthetic aperture imaging of concrete involve the application of 2D arrays [15][16][17][18] which employ shear waves for interrogation of the medium. Condition monitoring of tendon ducts using shear wave transducer arrays has been reported in [16,17], wherein the SAFT generated C-scan images of the scattered field are used to identify the embedded artificial defects as steel plate or air-voids. It is also demonstrated that the phase information corresponding to reflected signals can be used to distinguish http://dx.doi.org/10.1016/j.ultras.2015.05.008 0041-624X/Ó 2015 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation